Analyzing the Impact of Online Learning Material (OLM) on Students\' Academic Achievement With Special Reference to Private Universities in Malaysia - Yip, Yen San (2009)
This study attempts to identify the key factors which influence the effectiveness of OLM have any significant impact on the students\' academic achievement in private instituitions of higher learning in Malaysia.